Revised checklist of the butterflies of Serbia (Lepidoptera: Papilionoidea) - Popović, Miloš; Verovnik, Rudi (Zootaxa, 2018)
With studies spanning almost two centuries, butterflies are one of the best known insect groups in Serbia. However, there are still several inconsistencies regarding the number and selection of species included in national checklists published in the last decades. In order to overcome the confusing situation we provide a taxonomically up-to-date checklist of the butterflies for the country, including Kosovo, based on a comprehensive survey of the literature, inspection of available museum collections and from intensive field surveys over the last twenty years. Our aim is also to resolve some long standing problems with species potentially occurring in the country. For this purpose genitalia dissections and DNA barcoding have been used for identification where necessary. The annotated checklist includes 199 species of which Carcharodus orientalis is new for the country and the recently discovered white Anthocharis damone is listed for the first time. We also provide conclusive evidence of the presence of Melitaea ornata in Serbia. Among species listed in the previous species lists we excluded eight species due to inconclusive evidence, and provide a detailed explanation for their exclusion. We hope this publication will stimulate further studies of this important bioindicator group of insects and provide the basis for their conservation in the country.